Analysis of Related Factors of Tumor Recurrence or Progression After Transnasal Sphenoidal Surgical Treatment of Large and Giant Pituitary Adenomas and Establish a Nomogram to Predict Tumor Prognosis - Chen, Yike; Cai, Feng; Cao, Jing; Gao, Feng; Lv, Yao; Tang, Yajuan; Zhang, Anke; Yan, Wei; Wang, Yongjie; Hu, Xinben; Chen, Sheng; Dong, Xiao; et al. (Frontiers in Endocrinology, 2021)
Background: Pituitary adenoma (PA) is a benign neuroendocrine tumor caused by adenohypophysial cells, and accounts for 10%-20% of all primary intracranial tumors. The surgical outcomes and prognosis of giant pituitary adenomas measuring ≥3 cm in diameter differ significantly due to the influence of multiple factors such as tumor morphology, invasion site, pathological characteristics and so on. The aim of this study was to explore the risk factors related to the recurrence or progression of giant and large PA after transnasal sphenoidal surgery, and develop a predictive model for tumor prognosis. Methods: The clinical and follow-up data of 172 patients with large or giant PA who underwent sphenoidal surgery at the Second Affiliated Hospital of Zhejiang University School of Medicine from January 2011 to December 2017 were retrospectively analyzed. The basic clinical information (age, gender, past medical history etc.), imaging features (tumor size, invasion characteristics, extent of resection etc.), and histopathological characteristics (pathological results, Ki-67, P53 etc.) were retrieved. SPSS 21.0 software was used for statistical analysis, and the R software was used to establish the predictive nomogram. Results: Seventy out of the 172 examined cases (40.7%) had tumor recurrence or progression. The overall progress free survival (PFS) rates of the patients at 1, 3 and 5 years after surgery were 90.70%, 79.65% and 59.30% respectively. Log-rank test indicated that BMI (P < 0.001), Knosp classification (P<0.001), extent of resection (P<0.001), Ki-67 (P<0.001), sphenoidal sinus invasion (P=0.001), Hardy classification (P=0.003) and smoking history (P=0.018) were significantly associated with post-surgery recurrence or progression. Cox regression analysis further indicated that smoking history, BMI ≥25, Knosp classification grade 4, partial resection and ≥3% Ki-67 positive rate were independent risk factors of tumor recurrence or progression (P＜0.05). In addition, the nomogram and ROC curve based on the above results indicated significant clinical value. Conclusion: The postoperative recurrence or progression of large and giant PA was related to multiple factors and a prognostic nomogram based on BMI (≥25), Knosp classification (grade 4), extent of resection (partial resection) and Ki-67 (≥3%) can predict the recurrence or progression of large and giant PA after transnasal sphenoidal surgery.